2000
DOI: 10.1176/appi.ajp.157.8.1317
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of the Use of Compensatory Strategies to Enhance Adaptive Functioning in Outpatients With Schizophrenia

Abstract: Compensatory strategies may improve outcomes for patients with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
129
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(133 citation statements)
references
References 13 publications
2
129
0
2
Order By: Relevance
“…The adjective neurocognitive was chosen to indicate that the primary target of training was elemental neurocognitive mechanisms, and results of a preliminary functional magnetic resonance imaging (fMRI) study suggest evidence of a correspondence between improvement in neurocognition and favorable changes in brain function [25]. NET contrasts with other types of training that emphasize executive [26][27], compensatory [28][29], cognitive-behavioral [30][31], or gistful learning [32][33] training. However, all these approaches may share common features, and whether the presumed mechanism of change for each method is actually responsible for the favorable outcomes that have been reported remains largely unknown.…”
Section: Similarities and Differences With Other Cognitive Rehabilitamentioning
confidence: 99%
“…The adjective neurocognitive was chosen to indicate that the primary target of training was elemental neurocognitive mechanisms, and results of a preliminary functional magnetic resonance imaging (fMRI) study suggest evidence of a correspondence between improvement in neurocognition and favorable changes in brain function [25]. NET contrasts with other types of training that emphasize executive [26][27], compensatory [28][29], cognitive-behavioral [30][31], or gistful learning [32][33] training. However, all these approaches may share common features, and whether the presumed mechanism of change for each method is actually responsible for the favorable outcomes that have been reported remains largely unknown.…”
Section: Similarities and Differences With Other Cognitive Rehabilitamentioning
confidence: 99%
“…Treatment as usual in the Danish study consisted of ACT, which can be suggested to already be a very strong intervention. The frequency of home-visits (weekly) was similar to that of the active control conditions in two earlier US studies (Velligan et al, 2000;Velligan et al, 2002). However, therapy time in these US studies was primarily dedicated to the decoration of the patients' home, by the selection of items that have no direct relationship with cognition or daily functioning (e.g., wall posters, flowers).…”
Section: Dear Editorsmentioning
confidence: 81%
“…If replicated, such strategies can be potential game-changers in providing cognitive training for individuals with schizophrenia in low-resource settings. Cognitive adaptation training aims to bypass the cognitive deficits that adversely affect patients' everyday functioning [19]. Research is under way to explore if such interventions, delivered by nurses, could be cost-effective strategies to improve functionality of patients [20].…”
Section: Cognitive Training In Schizophrenia: Public Health Perspectivementioning
confidence: 99%